ML-Driven Optimization Framework for the Analysis, Design, and Development of Efficient Wireless Power Transfer Systems for EV Charging - Maridas Pillai; Anil Pal; Mukesh Kumar Gupta (International Journal of Manufacturing and Production Engineering, 2026)
The fast uptake of electric vehicles (EVs) has heightened the necessity of effective, dependable and convenient charging systems. The Wireless Power Transfer (WPT) systems can be taken as a potential solution as they allow charging cells without contact, without any risks, and without any overcrowding; the efficiency of the system is strongly influenced by the alignment of coils, the fluctuations of air-gaps, the conditions of the loads, and geometrical arrangements of the system. The study offers an optimization framework of WPT systems based on the analysis, design, and optimization of its performance to serve EV charging purposes with the involvement of Machine Learning (ML). Under the proposed method, the deep learning regression model is trained to be able to predict the power transfer efficiency in different operational conditions with a high degree of accuracy with R 2 = 0.994. The model helps in maximizing major parameters in coil alignment tolerance, air-gap levels, and magnetic coupling. The experimental and simulated outcomes prove that the ML-optimal system can give up to 6.9% transfer efficiency improvement, 14-percent gain in output power, and 20-percent shorter EV charge time than traditional design methods. Moreover, the enhancement of the field uniformity and the enhancement of the coupling are justified by the magnetic flux density distribution analysis that supports the optimization of coil geometry. The suggested ML based framework shows scalable and smart design approach that can greatly enhance the performance of real world WPT system and thus it is most suitable to current generation smart and autonomous EV charging systems.
Keywords: Efficiency Enhancement; Electric Vehicle Charging; Machine Learning Optimization; inductive power transfer; wireless power transfer